Conjugates of adenosine mimetics and arginine‐rich peptides serve as inhibitors and fluorescent probes but not as long‐lifetime photoluminescent probes for protein arginine methyltransferases. (28th October 2022) - Lavogina, Darja; Nasirova, Naila; Sõrmus, Tanel; Tähtjärv, Taavo; Enkvist, Erki; Viht, Kaido; Haljasorg, Tõiv; Herodes, Koit; Jaal, Jana; Uri, Asko
Abstract : The conjugates of an adenosine mimetic and oligo‐l ‐arginine or oligo‐d ‐arginine (ARCs) were initially designed in our research group as inhibitors and photoluminescent probes targeting basophilic protein kinases. Here, we explored a panel of ARCs and their fluorescent derivatives in biochemical assays with members of the protein arginine methyltransferase (PRMT) family, focusing specifically on PRMT1. In the binding/displacement assay with detection of fluorescence anisotropy, we found that ARCs and arginine‐rich peptides could serve as high‐affinity ligands for PRMT1, whereas the equilibrium dissociation constant values depended dramatically on the number of arginine residues within the compounds. The fluorescently labeled probe ARC‐1081 was displaced from its complex with PRMT1 by both S ‐adenosyl‐l ‐methionine (SAM) and S ‐adenosyl‐l ‐homocysteine (SAH), indicating binding of the adenosine mimetic of ARCs to the SAM/SAH‐binding site within PRMT1. The ARCs that had previously shown microsecond‐lifetime photoluminescence in complex with protein kinases did not feature such property in complex with PRMT1, demonstrating the selectivity of the time‐resolved readout format. When tested against a panel of PRMT family members in single‐dose inhibition experiments, a micromolar concentration of ARC‐902 was required for the inhibition of PRMT1 and PRMT7. Overall, our results suggest that the compounds containing multiple arginine residues (including the well‐known cell‐penetrating peptides) are likely to inhibit PRMT and thus interfere with the epigenetic modification status in complex biological systems, which should be taken into consideration during interpretation of the experimental data. Abstract : Conjugates of an adenosine mimetic and oligo‐l ‐arginine or oligo‐d ‐arginine (ARCs) and their fluorescent derivatives were explored in biochemical assays with members of the protein arginine methyltransferase (PRMT) family. The ARCs and arginine‐rich peptides could serve as high‐affinity ligands for PRMT1. A micromolar concentration of ARC‐902 was required for the inhibition of PRMT1 and PRMT7.